Specifics of the marketing audit in the financial-banking sector - De CECCO, Corrado; CETINĂ, Iuliana; RĂDULESCU, Violeta; DRĂGHICI, Mircea (Annals of Spiru Haret University. Economic Series, 2010)
Broadly speaking, the literature on the marketing audit and marketing of services has developed on a separate track. The prerequisite for a particular framework in developing the marketing audit of services is that it does not take sufficient account on the services features, even if the marketing audit is similar with the one in services, too. This thing does not allow the company of services to benefit from the advantages of the audit marketing.